Martin Geoffrey Low. 27 July 1950—6 August 2013. (8th December 2018) - Michell, Bob; Ferguson, Mike
Abstract : The young Martin Low embarked on research just as an influential review of biological membrane structure opened by stating that 'Biological membranes play a crucial role in almost all cellular phenomena, yet our understanding of the molecular organization of membranes is still rudimentary' (Singer & Nicholson 1972 Science 175, 720–731 (doi:10.1126/science.175.4023.720 )). Much of this ignorance was dispelled during the next couple of decades, the period during which he played a central role in establishing that many proteins on the surfaces of eukaryotic cells are moored there by membrane-embedded anchors consisting of glycosylated inositol phospholipids (known as GPI anchors). Martin started this work in Birmingham, UK, and then moved to the USA, working mainly in Ithaca, Oklahoma City and New York. During the latter period he became the focal person of this emerging research community. He provided reagents for and collaborated with a remarkable number of geographically scattered biochemists, immunologists and geneticists, and it was through him that most of the new information flowed. His generosity, modesty and scientific integrity were essential for the speedy maturation of this research area during the 1980s. Tragically, his work was cut short by early-onset Alzheimer's disease, and he retired prematurely in 2008. He died in 2013 at the appallingly young age of 63.